Automated Hybrid TACT® Volume Reconstructions - Linnenbrügger, N. I.; Webber, R. L.; Kobbelt, L. P.; Lehmann, T. M. (Methods of Information in Medicine, 2004)
Objectives: To design, implement in Java™, and evaluate a method and means for the automated localization of artificial landmarks in optical images for tuned-aperture computed tomography® (TACT®) that allows the replacement of radiographic with optical landmarks.Methods: Circular, colored, optical landmarks were designed to provide flexibility with regard to landmark constellation, imaging equipment, and lighting conditions. The landmark detection was based on Hough transforms (HT) for ellipses and lines. The HT for ellipses was extended to enable selective detection of bright ellipses on a dark background and vice versa, and the number of irrelevant votes in the accumulator arrays was reduced. An experiment was performed in vitro to test the automated landmark localization scheme, verify registration accuracy, and measure the required computation time.Results: A visual evaluation of the tomographic slices that were produced using the new method revealed good registration accuracy. A comparison to tomographic slices similarly produced by means of conventional TACT showed identical results. The algorithm ran sufficiently fast on standard hardware to allow landmark localization in “real time” during successive image acquisition in clinical applications.Conclusions: The proposed method provides robust automated localization of landmarks in optical images. Using a hybrid imaging system, TACT can now be clinically applied without manual interaction of a human operator and without radiopaque landmarks, which might cover anatomic details of diagnostic interest.
Keywords: Computer-assisted image processing; X-ray computed tomography; three-dimensional imaging